2020
DOI: 10.1016/j.appet.2019.104484
|View full text |Cite
|
Sign up to set email alerts
|

The impact of ‘on-pack’ pictorial health warning labels and calorie information labels on drink choice: A laboratory experiment

Abstract: Sugar-sweetened beverages (SSBs) are one of the largest added sugar sources to diets in the UK and USA. Health warning labels reduce hypothetical selection of SSBs in online studies but uncertainty surrounds their impact on selection of drinks for consumption. Calorie information labels are also promising but their impact on SSB selection is unclear. This laboratory study assessed the impact on SSB selection of ‘on-pack’ labels placed directly on physical products: i. a pictorial health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 50 publications
1
38
1
Order By: Relevance
“…As reported earlier, nutrition warnings influenced adults (but not children) to choose products with a highly reduced sugar content. Lastly, Mantzari et al [61] investigated nutritional warnings to which fear appeal images were added, but failed to find any effect.…”
Section: Labelmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported earlier, nutrition warnings influenced adults (but not children) to choose products with a highly reduced sugar content. Lastly, Mantzari et al [61] investigated nutritional warnings to which fear appeal images were added, but failed to find any effect.…”
Section: Labelmentioning
confidence: 99%
“…Wegman et al [70] investigated labels indicating whether a beverage was low or high in calories, and concluded that people were more likely to take home a beverage that was low in calories. However, another study on the impact of calorie labels on packages of sugar-sweetened beverages concluded that such labels did not lead to any changes in people's drink choices [61].…”
Section: Labelmentioning
confidence: 99%
“…Of the remaining 1,006 records, 871 were excluded based on abstract screening, leaving 135 full-text articles assessed for eligibility. Twenty-one of these full-text articles (reporting on 26 individual experimental studies) were eligible for inclusion in the qualitative synthesis [22,23,[26][27][28][29]35,41,[44][45][46][47][48][49][50][51][52][53][54][55][56]. Of these, 19 articles (reporting on 23 individual experiments and representing 16,241 individuals) were included in the quantitative meta-analysis.…”
Section: Article Selectionmentioning
confidence: 99%
“…Meta-analysis revealed that sugary drink warnings led to beneficial effects for all 3 real-stakes behavioral endpoints (Table 4). Fig 4 shows the forest plot of the 4 experimental studies examining sugary drink purchase or selection behavior [28,45,53,56], the primary outcome. In meta-analysis of these studies, warnings led to lower purchases or selection of sugary drinks compared to control conditions Attention and noticing.…”
Section: Effects Of Sugary Drink Warningsmentioning
confidence: 99%
“…They were told they would need to consume all of their chosen snackin line with the cover story that the study was examining the effect of snacking on cognitive performance (although in practice if a participant expressed a wish to stop eating, the researcher moved them on to the next part of the study). After participants had selected their snack, they were asked to also select a drink as part of an add-on study (reported elsewhere: [33]). Finally, after eating their snack (and consuming as much of the drink as they wanted to), participants repeated the Stroop task, before completing questions on their demographic variables.…”
Section: Food Appealmentioning
confidence: 99%